Socio-Legal Analysis Of The Utilization Of Letter Of Credit In International Business Transactions In Batam City - Seroja, Triana Dewi; Shahrullah, Rina Shahriyani; Kurniawan, Jefri (Universitas Negeri Gorontalo, 2023)
The provisions governing the Letter of Credit (L/C) in the form of customs and practices commonly used in international trade are called the Uniform Customs and Practice for Commercial Documentary Credit (UCP), issued by the International Chamber of Commerce (ICC). This research aims to analyze the effectiveness issues of the letter of credit in international transactions in the banking sector using Soerjono Soekanto's Theory of Legal Effectiveness. The research adopts empirical legal research through a socio-legal approach. Primary data is obtained from in-depth interviews, while secondary data is collected from literature studies. All data are analyzed using qualitative methods. It has been found that the application of the Letter of Credit (L/C) in international transactions in the banking sector in Batam City is not effectively implemented based on legal factors, law enforcement factors, and societal factors. There are still obstacles and solutions needed for the creation of an effective Letter of Credit (L/C) in international transactions in the banking sector in Batam City